ÅCómo el espacio público dispone las dinámicas de un sitio? (2017)
"The neighborhood Ciudad de Kennedy in Bogotá Colombia, is put on a comparative test, based on the development through the years since the foundation of the neighborhood, the principal themes are mobility and public space; this test was made in order to point out conclusions about the future emergence of the flyover metro in relation with the place, in spite of designing in a correct way the future Kennedy station, having in mind that all the future stations will become centers of services not only for the population who lives there but to the whole city. There is a significative lost of free space in the neighborhood, the design proposes accordingly to the problems of the place, a public space in which the neighborhood and its activities can be connected with the metro, the public space is also in ability to receive the flows that are produced by the metro." -- Tomado del Formato de Documento de Grado.